Value Chain Analysis of Broiler Poultry Production in Sindhuli District, Nepal - Khadka, Amita; Chaulagain, Rupendra (Nepalese Journal of Agricultural Sciences, 2025)
Poultry farming plays a crucial role in the economic and nutritional security of Nepal, with broiler production serving as a significant component of this sector. However, the broiler poultry value chain in Sindhuli District faces various challenges, including inefficiencies in production and marketing. This study aimed to analyze the value chain of broiler poultry production in Sindhuli District to identify key processes, challenges, and opportunities for improvement. The study was carried out during May-September 2023 through questionnaire format. Out of 55 respondents, 40 broiler poultry farms, 1 hatchery (broilers), 2 agro-vets and 10 retailers were surveyed where 5 core processes (input supply, production, collection, marketing, and consumption) were identified. Among the poultry farmers, 63% were male and 37% females. This study revealed a strong correlation between age and experience, emphasizing the pivotal role of experience in poultry farming. Educational backgrounds varied widely, with 27% respondents having only elementary education and only 3% respondents having attained a University-level education. Farm registration patterns followed distinct peaks in 2074, 2076, and 2077, reflecting the evolving landscape of poultry farming. Small-scale poultry operations, managing 500-1000 birds, dominated the sector. The intensive deep litter housing systems were found to be adopted by 100% of broiler framers at different scale and there was reliance on commercial feeds from sources outside the district. The respondents exhibited responsible antibiotic usage, with 90% farmers administering antibiotics therapeutically. A total of 70% farmers reported disease incidences on their farms, with Colibacillosis, Chronic Respiratory Disease (CRD), Infectious Bursal Disease (IBD), Newcastle Disease (ND), and Mycotoxicosis being the most encountered issues. This study identified challenges such as limited disease preparedness and biosecurity measures, small-scale poultry farming, restricted financial resources and opportunities for enhanced training, improving marketing channels and greater adoption of biosecurity practices.